Analytical and empirical methods for the characterisation of the permanent transverse displacement of quadrangular metal plates subjected to blast load: Comparison of existing methods and development of a novel methodological approach. (August 2021) - Lomazzi, L.; Giglio, M.; Manes, A.
Highlights: Estimation of the mid-point permanent deflection of a metallic plate subject to impulsive loading. Comparison of two consolidated analytical methods (Jones's theory and Nurick and Martin's method). New equations obtained via model fitting to numerical results from Analytical-Lagrangian analyses. Abstract: The behaviour of blast loaded structures has been extensively investigated over the past fifty years through experimental tests. These tests are quite challenging and require dedicated infrastructures to be efficiently and safely performed, however, the obtained data are useful to develop predictive approaches. Among them, analytical approaches are capable of efficient and satisfactory characterisation of blast events and the related effects on structures. In particular, among the analytical methods two categories can be identified: those methods exploiting fully analytical relationships, e.g., the Jones' theory, and those based on model fitting to experimental results, e.g., the Nurick and Martin's method. More recently, numerical models have been proposed to define the response of structures to blast loads: the main numerical methods considered to assess the structural response to blast loading are the coupled Eulerian-Lagrangian, uncoupled Eulerian-Lagrangian and Analytical-Lagrangian analyses. In this context, this paper aims at establishing a detailed comparison of the main fully analytical and empirical methods available in the literature, exploiting consolidated experimental evidence and results from numerical simulations. The focus of this work is on the estimation of the permanent transverse deflection of a quadrangular, initially flat plate subjected to blast loading, considering both close-range and far-field explosions. Moreover, a modelling framework is herein presented, which serves as a fast and reliable predictive tool for estimating blast load effects on plates.